2013
DOI: 10.1007/s10461-013-0527-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Group Sex Among a Community-Based Sample of Men Who Have Sex With Men (MSM) in Washington, DC

Abstract: Participation of MSM in group sex events (GSEs) is an understudied phenomenon. Studies on GSEs identified significant proportions of MSM engaging in unprotected anal intercourse (UAI). We sought to identify the prevalence of group sex participation among MSM in Washington, DC and to characterize these experiences. Data were collected for NHBS-MSM-3 in 2011. More than one-quarter of MSM (27.2 %) reported engaging in group sex in the prior year, with one-third reporting no condom use with their sex partners (33.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 23 publications
4
25
1
Order By: Relevance
“…Although more research is warranted to determine the true prevalence of GSE attendance among MSM in the US (2, 3, 6), it is clear that a substantial proportion of MSM are engaging in GSEs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although more research is warranted to determine the true prevalence of GSE attendance among MSM in the US (2, 3, 6), it is clear that a substantial proportion of MSM are engaging in GSEs.…”
Section: Discussionmentioning
confidence: 99%
“…Among MSM, engagement in GSEs is prevalent. One study in Washington, DC found that 27.2% of venue-attending MSM had participated in at least one GSE in the prior year (2). A national study that used online recruitment from a sex-seeking website reported that 45.2% of MSM had attended a sex party (specifically, an organized or themed GSE) in the past year (3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…20–22 Unweighted analysis of MSM cycle data is consistent with previous national and local publications. 2326 …”
Section: Methodsmentioning
confidence: 99%